Peer Support in Critical Care: A Systematic Review. Issue 9 (September 2018) - Haines, Kimberley J.; Beesley, Sarah J.; Hopkins, Ramona O.; McPeake, Joanne; Quasim, Tara; Ritchie, Kathryn; Iwashyna, Theodore J.
Abstract : Objectives: Identifying solutions to improve recovery after critical illness is a pressing problem. We systematically evaluated studies of peer support as a potential intervention to improve recovery in critical care populations and synthesized elements important to peer support model design. Data Sources: A systematic search of Medical Literature Analysis and Retrieval System Online, Cumulative Index to Nursing and Allied Health Literature, PsychINFO, and Excertpa Medica Database was undertaken May 2017. Prospective Register of Systematic Reviews identification number: CRD42017070174. Study Selection: Two independent reviewers assessed titles and abstracts against study eligibility criteria. Studies were included where 1) patients and families had experienced critical illness and 2) patients and families had participated in a peer support intervention. Discrepancies were resolved by consensus and a third independent reviewer adjudicated as necessary. Data Extraction: Two independent reviewers assessed study quality with the Newcastle-Ottawa Scale and the Cochrane Risk of Bias Tool, and data were synthesized according to the Preferred Reporting Items for Systematic Reviews guidelines and interventions summarized using the Template for Intervention Description and Replication Checklist. Data Synthesis: Two-thousand nine-hundred thirty-two studies were screened. Eight were included, comprising 192 family members and 92 patients including adults (with cardiac surgery, acute myocardial infarction, trauma), pediatrics, and neonates. The most common peer support model of the eight studies was an in-person, facilitated group for families that occurred during the patients' ICU admission. Peer support reduced psychologic morbidity and improved social support and self-efficacy in two studies; in both cases, peer support was via an individual peer-to-peer model. In the remaining studies, it was difficult to determine the outcomes of peer support as the reporting and quality of studies was low. Conclusions: Peer support appeared to reduce psychologic morbidity and increase social support. The evidence for peer support in critically ill populations is limited. There is a need for well-designed and rigorously reported research into this complex intervention. Abstract : Supplemental Digital Content is available in the text.